Kontrowersje wokół diagnozy poziomu funkcjonowania poznawczego uczniów z uszkodzeniem narządu słuchu - Wiśniewska, Anna (Wydawnictwo Naukowe UAM, 2014)
This paper discusses the problem of the psychological assessment of hearing-impaired children in Poland. Its aim is to provide a guide to reliable and accurate instruments for IQ assessment of the Deaf. The author adopts a position that people who are deaf and for whom the PJM (Polish Sign Language) is the mother tongue, should be regarded as a cultural minority. The paper reviews all of the psychological tools used in Poland like WAIS-R and WISC-R scale to evaluate the level of cognitive functioning of the hard of hearing. Given the lack of appropriate assessment tools for measuring deaf children’s intelligence, many psychologists in Poland use testing methods that are not welladapted, e.g. they only account for the Polish culture and disregard the characteristics of the PJM. The article reveals the consequences of using such ill-adapted tests as well as assessing child’s learning difficulties based on them.
uczniów z uszkodzeniem narządu słuchu Levels of Students with a Hearing Impairment
Keywords: psychological assessment of the deaf; cultural adaptation of assessment tests; the Deaf; Polish Sign Language